2023
DOI: 10.1057/s41599-023-01527-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of functional, symbolic, and experiential image on approach behaviors among state-park tourists from India, Korea, and the USA

Abstract: This study provides insights into the influence of state park image, visitor emotions, and place identity on visitors’ revisit intentions by considering the moderating impact of national culture. A quantitative process with the data collected in India, Korea, and the US was used. Hierarchical regression analysis evidences the moderating role of national culture, which is hardly explored in the state park context. Results confirm that most hypotheses are fully or partially accepted, which suggests that brand im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…Place attachment theory (PAT) explains an individual's sense of attachment or belonging to a distinctive place (Gao et al, 2022). The components of PAT are traditionally classified into two dimensions, namely place identity (PI) and place dependence (PD; Gao et al, 2022;Singh et al, 2023). According to tourism researchers, PI and PD influence person-place relationships, and these factors are regarded as correlated but distinct subconstructs of attachment (Kostanski, 2011).…”
Section: Effect Of Place Attachment 1083mentioning
confidence: 99%
See 4 more Smart Citations
“…Place attachment theory (PAT) explains an individual's sense of attachment or belonging to a distinctive place (Gao et al, 2022). The components of PAT are traditionally classified into two dimensions, namely place identity (PI) and place dependence (PD; Gao et al, 2022;Singh et al, 2023). According to tourism researchers, PI and PD influence person-place relationships, and these factors are regarded as correlated but distinct subconstructs of attachment (Kostanski, 2011).…”
Section: Effect Of Place Attachment 1083mentioning
confidence: 99%
“…In sum, studies have indicated that PI and PD are place attachment constructs (e.g. Gao et al, 2022;Singh et al, 2023) and have divided the construct of PI into cognitive PI and affective PI (i.e. Kumar et al, 2020).…”
Section: Effect Of Place Attachment 1083mentioning
confidence: 99%
See 3 more Smart Citations